Expert System for Diagnosing Corn Plant Diseases Using the Web-Based Certainty Factor Method - Muhamad Masjun Efendi; Erfan Wahyudi; Juhartini; Ahmad Nazar (International Journal of Scientific Research, 2024)
In the process of corn plant growth, it often faces the threat of various diseases that can hinder optimal growth. Dealing with this issue often requires the presence of a plant expert, such as a field agricultural extension officer.  However, limitations in the human resources of  agricultural extension officers, time constraints, and geographical distances often make it difficult for farmers to get direct assistance from experts. To overcome these constraints, a system capable of addressing issues related to corn plant diseases, similar to the role of an expert, is needed. In this study, the Certainty Factor method is employed, suitable for an expert system that measures the level of uncertainty, and through testing with 28 sample data cases, the accuracy level of this system reaches 90%.